Sodium-Glucose Co-Transporter 2 Inhibitors Use Improves the Satisfaction With Anti-diabetic Agent Treatment: A Questionnaire-based Propensity Score-matched Study - Shi, Fang-Hong; Yue, Jiang; Jiang, Yi-Hong; Yang, Ming-Lan; Gu, Zhi-Chun; Ma, Jing; Li, Hao (Frontiers in Pharmacology, 2022)
Background: Specific safety issues with sodium-glucose co-transporter-2 (SGLT2) inhibitors such as infection, fractures, worsening of renal function and euglycemic ketoacidosis have been raised. Concerns about adverse events might limit the use of this drug class. The satisfaction with SGLT2 inhibitors treatment in Chinese patients with type 2 diabetes mellitus (T2DM) is unknown. Material and Methods: Patients with T2DM who visited the hospital between October 2019 and June 2020 were included in this retrospective analysis. Patients were divided into SGLT2 inhibitors used group or not. The Satisfaction with Oral Anti-Diabetic Agent Scale (SOADAS) questionnaire and self-reported AEs were obtained at 3 months of follow-up. Propensity score matching (PSM) was performed to adjust for confounding factors. Univariate and multivariable linear regression models were used to explore potential risk factors associated with overall satisfaction. Results: A total of 145 T2DM patients were included, with 76 SGLT2 inhibitors users and 69 non-users. Patients administered with SGLT2 inhibitors presented with increased overall satisfaction (mean [SE]: 22.8 [0.67] vs 20.6 [0.64], P = 0.016) and overall satisfaction rate (n [%]: 40 [52.6%] vs 21 [30.4%], P = 0.007) when compared to other anti-diabetic agents. The use of SGLT2 inhibitors significantly improved satisfaction of glycemic control ability (mean [SE]:3.9 [0.12] vs. 3.5 [0.12], P = 0.027), diabetic symptom’s control ability (3.5 [0.15] vs. 3.0 [0.15], P = 0.027), glycemic control speed (3.9 [0.11] vs.3.4 [0.12], P = 0.011), medication tolerability (3.9 [0.10] vs.3.5 [0.12], P = 0.012), and overall satisfaction (4.0 [0.11] vs.3.6 [0.12], P = 0.037), but it did not improve satisfaction of medication effect on bodyweight (3.8 [0.11] vs.3.4 [0.11], P = 0.166). After adjusting confounding factors (47 patients for each group), consistent results were obtained. No significant differences of self-reported clinical AEs were observed between SGLT2 inhibitors users and non-users. Multivariable regression analyses verified that the use of SGLT2 inhibitors was associated with increased levels of satisfaction. Conclusions: The use of SGLT2 inhibitors was associated with increased levels of satisfaction in T2DM patients, but not associated with overall clinical safety. Self-reported AEs were not related to the satisfaction with the use of anti-diabetic agents.